Transition Signals Used in Narrative Text - Yessy Marzona (Jurnal Ilmiah Langue and Parole, 2022)
The purpose of this research is to find out types and the dominant one of transition signals used in narrative text. This research aimed to find out the use of transitional signals in narrative text specifically to find out the types of transitional signals and the accuracy of its use. The method of this research is descriptive qualitative by doing library research. The data were collected by analyzing the transition signal used in five narrative texts. The transitional signals that were analyzed are transitional signals for adding ideas and emphasizing, showing contrast and comparison, showing cause and effect, providing examples, introducing time order or sequence, and concluding or summarizing. The results shows that the transition signals used in narrative text are the transition signal indicates time, comparison, additional idea, and contrast. The dominant transition signal used the transition signal indicates additional idea. The findings shows that the transition signal used on the narrative text is developed in a single central theme.